2008
DOI: 10.1086/588823
|View full text |Cite
|
Sign up to set email alerts
|

Salmonellosis Outcomes Differ Substantially by Serotype

Abstract: Salmonella serotypes are closely related genetically yet differ significantly in their pathogenic potentials. Understanding the mechanisms responsible for this may be key to a more general understanding of the invasiveness of intestinal bacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
306
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(343 citation statements)
references
References 21 publications
17
306
1
3
Order By: Relevance
“…Statistical analysis revealed that S. Enteritidis, S. Choleraesuis, and S. Typhi caused invasive Salmonella infection more frequently compared to 1,4, [5],12:i:-and S. Typhimurium. This conclusion is in accordance with those of others [27]. S. Enteritidis is the most frequently isolated Salmonella serotype in our local area, so we should pay attention to its features.…”
Section: Discussionsupporting
confidence: 93%
“…Statistical analysis revealed that S. Enteritidis, S. Choleraesuis, and S. Typhi caused invasive Salmonella infection more frequently compared to 1,4, [5],12:i:-and S. Typhimurium. This conclusion is in accordance with those of others [27]. S. Enteritidis is the most frequently isolated Salmonella serotype in our local area, so we should pay attention to its features.…”
Section: Discussionsupporting
confidence: 93%
“…Salmonella enterica is highly diverse, containing over 2,500 different serovars. The representative serovars from this species are the most commonly isolated serovars during outbreaks of foodborne salmonellosis, including S. Enteritidis, S. Typhimurium, S. Virchow, and S. Infantis [24]. S. Enteritidis and S. Typhimurium are the most predominant isolated organisms in most Salmonella cases associated with the consumption of contaminated poultry, pork, and beef products [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, following the emergence of S. Enteritidis in the country, more invasive infections have been encountered than previously, particularly in patients with underlying diseases. Previously published studies have shown that S. Enteritidis are among a few serotypes that are associated with a higher risk of extra-intestinal infection [16,17]. Immunocompromised patients are also known to be at higher risk for the development of bacteremia with this serotype [17].…”
Section: Discussionmentioning
confidence: 99%